Английские заимствования в языке немецкой рекламы - Ступакова, Н.А. (Культура народов Причерноморья, 2013)
В данной статье анализируются особенности функционирования англицизмов в немецком языке, что в целом помогает определить некоторые тенденции языковых изменений. Научная новизна данной темы заключается в том, что проведен анализ мало изученного ранее пласта лексики – англицизмов в языке немецкой рекламы. На основе проанализированного материала предпринята попытка дать оценку современной языковой ситуации в Германии. Целью данной статьи является определение степени влияния английского языка на язык немецкой рекламы. Для решения задач применяются следующие методы лингвистического анализа: метод сплошной выборки, метод структурного анализа собранного материала, сопоставительный метод. Ключевые слова: англицизм, слоган, заимствование, реклама. У даній статті аналізуються особливості функціонування англіцизмів в німецькій мові, що в цілому допомагає визначити деякі тенденції мовних змін. Наукова новизна даної теми полягає в тому, що проведений аналіз мало вивченого раніше пласта лексики - англіцизмів у мові німецької реклами. На основі проаналізованого матеріалу зроблено спробу дати оцінку сучасної мовної ситуації в Німеччині. Метою даної статті є визначення ступеня впливу англійської мови на мову німецької реклами. Для вирішення завдань застосовуються такі методи лінгвістичного аналізу: метод суцільної вибірки, метод структурного аналізу зібраного матеріалу, порівняльний метод. Ключові слова: англіцизм, слоган, запозичення, реклама. This article examines the peculiarities of English loan words in German language, which generally helps to identify some of the trends of language changes. Language of advertizing is closely connected with language changes and reflects the main tendencies of language development. Language of German advertizing includes a large number of anglicisms that is noticeable on the example of slogans which either are completely written in English, or include English words and expressions. Relevance of a subject is caused by its communication with one of important problems of modern linguistics – research of actual language units in speech. Foreign loans represent huge research interest for linguists of our time. This article is devoted to english loan words in German (on a material of advertizing slogans). The subject of english loan words in German is rather popular and became object of studying for many both domestic, and foreign linguists. Scientific novelty of the topic is that the analysis of the previously little-studied layer of vocabulary has been made - Anglicisms in German language of advertising. On the basis of the analyzed material was made an attempt to estimate a current linguistic situation in Germany. The aim of this article is to determine the level of influence of English on German language of advertising. To solve the problems, the following methods of linguistic analysis have been used: the method of continuous sampling, a method of structural analysis of the collected data, a comparative method. Keywords: Anglicism, slogan, loanword, advertising.